Analisis Gaya Bahasa Dalam Lagu "Belenggu” dan “Ku Kira Kau Rumah” Amigdala - Hermayanti Purnama Sari; Salma Aina Rasyid (Ta'rim: Jurnal Pendidikan dan Anak Usia Dini, 2022)
Language is an important self-identity of a country. Because language is used as a means of communication with each other. This figure of speech is a part of language. In making short stories, poetry, literary works, scripts, and novels, figure of speech is often used. Not only that figure of speech is also often used by people in everyday life. But it is rare for parents to use figure of speech, usually often used by teenagers. As has been conveyed from the definition above. The purpose of this study is to discuss knowing and understanding the meaning of the figure of speech contained in the song "Shackles" by Amygdala. The research used is descriptive qualitative method. The data in this study is in the form of the lyrics of the song Belenggu. The analysis technique uses stylistic analysis which is a science that examines the analysis of the meaning and style of language in literature. The results of each verse of song lyrics store different meanings and figures of speech such as parallelism, metaphor, personification, and hyperbole